2000
DOI: 10.1093/clipsy.7.4.435
|View full text |Cite
|
Sign up to set email alerts
|

Interparental agreement on internalizing, externalizing, and total behavior problems: A meta-analysis.

Abstract: Previous studies have addressed the degree of correspondence between interparental reports of children's behavior problems, but have not examined the discrepancies in these reports. A meta‐analysis containing 60 studies and 126 independent effect sizes was conducted. Results suggest that maternal and paternal ratings exhibit moderate correspondence in ratings of internalizing behavior problems in children and large correspondence in ratings of externalizing and total behavior problems in children. In terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
205
6
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(249 citation statements)
references
References 92 publications
34
205
6
4
Order By: Relevance
“…These findings are consistent with the results of many other studies on cross-informant agreement on the ASEBA scales [2,14,23,42,69]. Our main result on discrepancy, namely that mothers reported more symptomatic problem behaviour than kindergarten teachers and therapists, is also in line with the existing literature [40,69].…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with the results of many other studies on cross-informant agreement on the ASEBA scales [2,14,23,42,69]. Our main result on discrepancy, namely that mothers reported more symptomatic problem behaviour than kindergarten teachers and therapists, is also in line with the existing literature [40,69].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings were consistent with a study on school-aged children and their parents after a medical traumatic event [27], but differed from a Each parent could describe more than one concern. Percentages in each cell are expressed as proportions of the total number of participating parents at the respective stages Eur Child Adolesc Psychiatry previous study that only found a relationship between mother-reported child and maternal adjustment after a paediatric burn event [17]. However, it should be mentioned that the father's perspective on child adjustment in that study was absent [11].…”
Section: Discussionmentioning
confidence: 96%
“…Moreno and colleagues [16] have argued that ''the scarcity of father involvement in psychological research has likely yielded an incomplete picture of the familial context involved in child and adolescent psychopathology, especially in the assessment of youth's internalising and externalising behaviour problems'' (p. 915). Mothers and fathers may hold a different view of their child's behaviour [16], although it has been found that mothers and fathers overall show moderate to high levels of agreement concerning their child's internalising and externalising behaviour problems [17]. Up to now, studies on children with burns did not address the degree of interparental agreement or discrepancy on ratings of child internalising and externalising behaviour problems.…”
mentioning
confidence: 99%
“…Most studies have found that agreement is lower, or discrepancies are greater, among informants' ratings of African American children compared with informants' ratings of European American children (Kaufman et al, 1980;Wachtel, Rodrigue, Geffken, Graham-Pole, & Turner, 1994;Walton, Johnson, & Algina, 1999; Youngstrom, Loeber, & StouthamerLoeber, 2000). However, a meta-analysis that focused specifically on mother-father agreement did not find a relation between informant agreement and ethnicity (Duhig et al, 2000). In addition, some recent work has not found ethnic differences in the degree of discrepancies among informants' ratings but in differences in the direction of discrepancies among informants' ratings: Whereas African American children rate themselves as more anxious than their mothers rate them, European American children rate themselves as less anxious than their mothers rate them (Wachtel et al, 1994;Walton et al, 1999).…”
mentioning
confidence: 84%